Emotion in languaging: languaging as affective, adaptive, and flexible behavior in social interaction - Jensen, Thomas W. (Frontiers in Psychology, 2014)
This article argues for a view on languaging as inherently affective. Informed by recent ecological tendencies within cognitive science and distributed language studies a distinction between first order languaging (language as whole-body sense making) and second order language (language as system like constraints) is put forward. Contrary to common assumptions within linguistics and communication studies separating language-as-a-system from language use (resulting in separations between language vs. body-language and verbal vs. non-verbal communication etc.) the first/second order distinction sees language as emanating from behavior making it possible to view emotion and affect as integral parts languaging behavior. Likewise, emotion and affect are studied, not as inner mental states, but as processes of organism-environment interactions. Based on video recordings of interaction between 1) children with special needs, and 2) couple in therapy and the therapist patterns of reciprocal influences between interactants are examined. Through analyzes of affective stance and patterns of inter-affectivity it is exemplified how language and emotion should not be seen as separate phenomena combined in language use, but rather as completely intertwined phenomena in languaging behavior constrained by second order patterns.